Assessment of actual laser emission at 532nm in tattoo removal devices - Rubens Pontello Junior; Jerry Cristian Gandin; Kamelyn Caroline Casagrande (Sociedade Brasileira de Dermatologia (SBD), 2024)
xxxxxxxxxxxxx